Computer literacy through dance: the dancing computer project. Issue 1 (3rd April 2017) - Owen, Charles B.; Dillon, Laura; Dobbins, Alison; Rhodes, Matthew; Levinson, Madeline; Keppers, Noah
Abstract : Purpose: The purpose of this paper is to present the design and evolution of the Dancing Computer project. Dancing Computer is an ongoing research project at the Michigan State University, which is developing a system that aims to increase computer literacy in elementary-aged children by teaching them first to read code before they write it. The main objective is to educate children on basic concepts of computer science. Design/methodology/approach: Children are given tablet computers that present a simple program line-by-line that they execute as they pretend to be a computer. The programs are acted out on a portable dance floor consisting of colored tiles, and the program statements instruct the child to move, turn and act out dance poses and terminology. Findings: The Dancing Computer prototype was tested in six different locations in 2016, reaching approximately 250 students. Learning was demonstrated by significant improvements in both task duration and error performance as students performed the activities. The most common errors were movement errors, where participants failed to move the correct number of squares. Social implications: This project has the potential to increase the level of computer literacy for thousands of children. This project's goal is to increase understanding of what a computer does, what a program does and the step-by-step nature of computer programs. Originality/value: This is a unique and a different approach – the norm being to start students off writing code in some language. In Dancing Computer stages children as readers of programs, allowing them to pretend to be a computer in a fun and engaging activity while also learning how computers execute real programs.